Lesões musculoesqueléticas, carga de treinamento e recuperação durante o treinamento básico militar da Academia da Força Aérea - Castro, Phelipe Henrique Cardoso de (2022)
As soon as they enter the military institutions, all individuals are obligatorily submitted to a rigorous period, called Basic Military Training (BMT). In this sense, the present study aimed to evaluate and characterize musculoskeletal injuries, training load, recovery, creatine kinase (CK) concentration and skin temperature during the BMT of the Air Force Academy (AFA). This is a longitudinal study, carried out during the AFA TBM, lasting 37 days. To verify the musculoskeletal injuries that occurred during training, a daily survey of medical and physiotherapeutic records was carried out. After the military training instructions, the participants were evaluated through the subjective perception of exertion (SPE) and once a day, always before the first activity, they were asked about the current stage of recovery using the total quality of recovery scale (TQR). From the SPE, the total weekly training load (TWTL) and the monotony index were calculated. In the pre-BMT period and at the end of each week, CK concentrations and skin temperatures were measured. A total of 103 male soldiers were evaluated. During the BMT, 121 musculoskeletal injuries were recorded, which were suffered by 64.1% (n=66) of the military. The body region with the highest frequency of injuries were the lower limbs (75.2%). Of the participants who suffered at least one musculoskeletal injury, 42.4% (n=28) were excused from activities for at least one day. The TWTL of week 2, 20010.1±4010.1 (U.A), was the lowest when compared to the others (p<0.001). The weekly averages found for monotony were higher than 2.6±0.5. For TQR, the second week was the one with the worst recovery (11.5±1.6) (p<0.001). CK increased right at the beginning of training and remained throughout the BMT with values higher than the initial assessment. Bilateral asymmetries greater than 0.5º were found in several body regions, with the knee being the most affected region. A positive correlation was found between CK and the temperature of the biceps, pectorals and knees, but only in a few weeks. The findings of the present study indicate that the TBM had a high percentage of injuries, with the lower limbs being the most affected region. The weekly training loads were high, showed no progression and had high monotony. Recovery throughout the stage was not adequate. CK increased at the beginning of the stage and remained high. Skin temperature showed asymmetries, but these did not correlate with CK concentration.